Structural mapping of Enceladus and implications for formation of tectonized regions. Issue 5 (26th May 2015) - Crow‐Willard, Emma N.; Pappalardo, Robert T.
Abstract Global structural mapping of high‐resolution Cassini images of Enceladus reveals a richly varied surface. Most notable are three main regions of deformation each containing multiple structural units. In addition to the well known "South Polar Terrain" (SPT), there are two other large regions of deformation that we term "Leading Hemisphere Terrain" (LHT) and "Trailing Hemisphere Terrain" (THT). Each of these three terrains includes a circumferential belt that encloses one or more other structurally deformed units. Areal extents range from about 80, 000 km2 (SPT) to 195, 000 km2 (LHT) or 160 to 250 km equivalent circular radius. Based on relative crater densities, the THT is inferred to be older than the LHT; the geologically active SPT is the youngest. The overall similarities in shape and dimension of the three tectonized terrains suggest similar formational processes, plausibly related to broad loading of a thin elastic shell. A viable scenario is that each tectonized terrain formed above a large‐scale region of warm upwelling ice, with subsequent downwarping triggered by cooling and/or subsurface melting. However, differences in morphological detail suggest that the specific evolution of each tectonized terrain has been different.